Prevalence of common mental disorders in university students during the COVID-19 pandemic - Carvalho, Ianny Soares de; Araujo-Filho, Augusto Cezar Antunes; Silva, Andréa Pereira da; Ibiapina, Aline Raquel de Sousa; Cardoso, Adelzira Rodrigues; Rocha, Silvana Santiago da (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2023)
Objective: to verify the prevalence of common mental disorders among university studentsat a public higher education institution in the south of Piauí, during the COVID-19 pandemic.Methodology: this is a cross-sectional and descriptive-exploratory study with 303 universitystudents. Data were collected through online instruments, one on the sociodemographic andschool profile and the Self-Report Questionnaire. Associations between categorical variables weretested using Pearson’s chi-square test and Fisher’s exact test, with a significance level of 5%.Results: the prevalence of psychological distress was 58.7%. A predominance of symptomsof common mental disorders was observed in female, young and single individuals. There wasa greater predominance of symptoms of anxious depressive mood, in which the majoritycomplained of feeling nervous, tense or worried. Conclusion: suspicion of psychological distressis high among university students and, therefore, actions are needed to minimize the impacts onthe mental health of this population.